Dementia- and mild cognitive impairment-inclusive exercise: Perceptions, experiences, and needs of community exercise providers - Bechard, Lauren E. (PLoS One, 2020)
PURPOSE: For persons who are at risk for, or living with, dementia exercise is recommended, yet many become or remain inactive. Exercise providers play a vital role in promoting and facilitating exercise in these groups by recognizing and being responsive to the needs of persons with mild cognitive impairment (MCI) or dementia in exercise programming. The objective of this study was to explore the experiences, perceptions, and needs of community exercise providers regarding dementia. MATERIALS & METHODS: Five focus groups were held with community exercise providers (n = 30) who deliver exercise to older adults (≥55 years) in municipal, non-profit, for profit, or academic settings. RESULTS: Three themes were developed: (1) Unique experiences and diverse perceptions: suggests unique personal experiences with MCI and dementia inform distinct perceptions of dementia; (2) Dementia-Inclusive Practices: learning as you go and adapting for the individual: reflects exercise providers’ approaches to recognizing and accommodating individuals’ unique abilities and preferences; (3) Training and Best Practices, with Flexibility: identifies exercise providers’ desires for MCI- and dementia-specific knowledge and training strategies, which need to recognize dementia heterogeneity between and within persons over time. CONCLUSIONS: These findings highlight a willingness of exercise providers to support dementia-inclusive exercise, but recognize they have minimal training and lack educational resources to do so. Formal training resources may enhance exercise accessibility and participation for persons with MCI or dementia.